Use of Wolbachia to drive nuclear transgenes through insect populations. - Sinkins, S; Godfray, H (2004)
Wolbachia is an inherited intracellular bacterium found in many insects of medical and economic importance. The ability of many strains to spread through populations using cytoplasmic incompatibility, involving sperm modification and rescue, provides a powerful mechanism for driving beneficial transgenes through insect populations, if such transgenes could be inserted into and expressed by Wolbachia. However, manipulating Wolbachia in this way has not yet been achieved. Here, we demonstrate theoretically an alternative mechanism whereby nuclear rather than cytoplasmic transgenes could be driven through populations, by linkage to a nuclear gene able to rescue modified sperm. The spread of a 'nuclear rescue construct' occurs as long as the Wolbachia show imperfect maternal transmission under natural conditions and/or imperfect rescue of modified sperm. The mechanism is most efficient when the target population is already infected with Wolbachia at high frequency, whether naturally or by the sequential release of Wolbachia-infected individuals and subsequently the nuclear rescue construct. The results provide a potentially powerful addition to the few insect transgene drive mechanisms that are available.